Latest Developments in Magnetic Resonance Imaging for Evaluating the Molecular Microenvironment of Gliomas - Zhang, Hanwen; Zhang, Hongbo; Lin, Fan; Huang, Biao (Current Medical Imaging, 2024)
The 2021 World Health Organization (WHO) Classification of Tumors of the Central Nervous System has brought a transformative shift in the categorization of adult gliomas. Departing from traditional histological subtypes, the new classification system is guided by molecular genotypes, particularly the Isocitrate Dehydrogenase (IDH) mutation. This alteration reflects a pivotal change in understanding tumor behavior, emphasizing the importance of molecular profiles over morphological characteristics. Gliomas are now categorized into IDH-mutant and IDH wildtype, with significant prognostic implications. For IDH-mutant gliomas, the concurrent presence of Alpha-Thalassemia/mental retardation syndrome X-linked (ATRX) gene expression and co-deletion of 1p19q genes further refine classification. In the absence of 1p19q co-deletion, further categorization depends on the phenotypic expression of CDKN2A/B. Notably, IDH wildtype gliomas exhibit a poorer prognosis, particularly when associated with TERT promoter mutations, EGFR amplification, and +7/-10 co-deletion. Although not part of the new guidelines, the methylation status of the MGMT gene is crucial for guiding alkylating agent treatment. The integration of structural and functional Magnetic Resonance Imaging (MRI) techniques may play a vital role in evaluating these genetic phenotypes, offering insights into tumor microenvironment changes. This multimodal approach may enhance diagnostic precision, aid in treatment planning, and facilitate effective prognosis evaluation of glioma patients.
Keywords: Tumors